Some issues of agreements on the reorganization of a legal entity (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The author has outlined his own vision on certain issues that occur in the context of concluding contracts while the reorganization of a legal entity. Special attention is paid to the fact that the civil law does not provide answers on both issues of concluding relevant contractual structures, and does not determine their legal nature, procedure of conclusion and execution.The author believes that the reorganization of the legal entity, as a process of creation, is realized by the way of successive accumulation of a number of legal facts, which collectively form a legal structure that involves the reorganization of one or more existing legal entities and the emergence of one or more new subjects as successors.It has been proved that the agreement on the reorganization is not a statutory document of a legal entity, as supported by the recognition of the status of constituent document only by the statute of a core number of legal forms of legal entities. Consequently, we can not confirm that an agreement on the reorganization determines legal personality of the corporation.Compared to Ukrainian legal reality the process of concluding agreements on the reorganization of a legal entity in the UK, Germany and the US is more detailed. The Civil Code of Ukraine does not regulate the terms of these agreements, the procedure for their conclusion, changes and termination, and even does not mention them.The objective of the merger agreement is not creating a new legal entity, but providing the procedure for the transfer of the rights and duties of several existing legal entities to one legal entity, specially created for this.The parties of the merger agreement of business entities are not the members of newly created corporations, since their activities are terminated because of the creation of a new entity. We can not call them as founders, because founders – are persons, who make a decision on a corporate organization’s creation. The formation of a new business entity is not realized in the process of merger of business companies, it occurs within the process of reorganization.The inclusion of the agreements on the reorganization of legal entities into the structure of the Civil Code of Ukraine will make possible to gradate legal regulation of the processes of reorganization, will serve as a reliable guarantee of protecting the rights of their members (shareholders) and creditors.